Beat the Game: a Foucauldian exploration of coaching differently in an elite rugby academy. Issue 6 (24th July 2021) - Avner, Zoë; Denison, Jim; Jones, Luke; Boocock, Emma; Hall, Edward Thomas
ABSTRACT: Problem-based learning along with other game and player-centred approaches have been promoted as valuable alternatives to more traditional, skill-based, directive, and leader-centric pedagogical approaches. However, as research has shown, they are not unproblematic or straightforward to apply. Heeding to calls for more empirical studies of game-centred approaches in coaching contexts, this study explored the impact of a unique problem-based learning (PBL) informed academy-wide coaching approach to athlete learning and development known as Beat the Game within a top-level rugby union professional club. Drawing on Michel Foucault's ([1977]. Discipline and punish: The birth of the prison . Vintage) disciplinary framework, we specifically sought to critically examine whether, to what extent, and how a PBL informed academy-wide coaching approach challenges the dominant disciplinary logic of elite sport. Our data, based on observations and semi-structured interviews with three academy coaches and sixteen junior and senior academy players, showed a definitive loosening of disciplinary aspects in both training and game environments accompanied by a shift towards a less leader-centric, linear, and hierarchical understanding of leadership and decision-making. Despite these promising shifts, the application of a PBL-informed coaching approach within this elite development context also presented many challenges, not the least of which resulted from the non-alignment of academy and first team coaching approaches. Our analysis, therefore, indicated the need for more research which focuses on the short-term and long-term impact that such disconnects have on continued progression, performance, physical and mental wellbeing, and job satisfaction and longevity especially given the growing popularity of non-linear pedagogies in youth sporting contexts.